Availability of data on agrobiodiversity in South Asia: A report on data availability for Bangladesh, India, Nepal, and Pakistan - Kamal, Mustafa; Faisal, Asif Al; Druti, Baishakhee Pashari; Chakraborty, Shreya; Laing, Alison; Krupnik, Timothy J. (TAFSSA, 2023)
Global and local data consistency and interoperability is lacking for many crucial aspects of agrobiodiversity. Here we present a summary of public data availability for agrobiodiversity-related indicators of regional agrifood systems. Data have been drawn from surveys, reports and censuses in Bangladesh, India, Nepal, and Pakistan. This brief can be used by researchers, policymakers, and development planners to understand the data landscape and to identify measurement priorities for future data collection and curation efforts.